Intervensi Kebudayaan Lokal melalui Keterlibatan Pecalang dalam Mempengaruhi Penerapan Protokol Kesehatan CHSE terhadap Loyalitas Wisatawan ke Desa Budaya Kertalangu Denpasar - I Made Trisna Semara; I Nyoman Sunarta; I Made Sudjana (Universitas Udayana, 2022)
Applying the CHSE (Cleanliness, Health, Safety, Environment Sustainability) health protocol is a new practice that initially received a light rejection from the community, including when visiting tourist attractions during the pandemic Covid-19. This article aims to identify the application of CHSE, identify the effect of its application on tourist loyalty and identify local cultural interventions through the involvement of customary village security guard of ‘pecalang’ on the effect of the application of CHSE on tourist loyalty. This article used a quantitative approach, with data analysis techniques using quantitative descriptive and Partial Least Square (PLS) analysis. The results showed that the implementation of CHSE was carried out well, with an average rating of 4.09 (good), and had a positive and significant effect on tourist loyalty. The involvement of ‘pecalang’ certainly contributes to the implementation of CHSE in tourist attractions, but the uncontrolled involvement of ‘pecalang’ can reduce tourist loyalty.